Analysis of Locutionary and Perlocutionary Acts in Language Advertisements - Muhammad Ariq Naufal Salsabila; Lucky Herliawan Y. A.; Pepen Permana (IKIP Siliwangi, 2024)
Pragmatics in linguistics is the scientific study of the relationship between language and the context that underlies the explanation of the meaning or understanding of language. In pragmatics, there is a branch of science that discusses speech acts, which are divided into three categories: locutionary acts, which are only utterances delivered by speakers to state something; an illocutionary act is a speech act that has a specific purpose or context; perlocutionary acts are actions carried out by the speech partner as an effect of the speaker's speech. Speech acts do not only occur orally but also in writing, including scripts in advertisements.The research method used is qualitative and descriptive because the data collected doesn't involve statistical figures. This approach provides a narrative overview of the object and study results. The researcher acts as the instrument, collecting data on speech acts based on Austin and Nababan's theories. The results of the analysis show that in German-language advertisements, there are all types of speech acts. It is very important to learn and understand language, not only in terms of grammar but also in the context and meaning of the language to avoid misunderstandings.